USING ACTIVITIES IN TEACHING HIGH CLASS PUPILS - Urinboyeva Mavludaxon Alijon qizi; Kosimova Mukammal Umaraliyevna (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotation. This article provides evident issues about using activities in teaching high classes and also tries to find appropriate solutions to the given questions. It involves the theories of various researchers and the responses of interviewee’s which are based on their current status.